2017
DOI: 10.47941/ijf.58
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Credit Access for Firms in the Biogas Sub Sector in Kenya

Abstract: Purpose: The purpose of this study was to determine the factors influencing credit access for firms in the biogas sub sector in Kenya.Methodology: The study adopted descriptive survey. The target population of the study was the firms in biogas sub sector in Kenya. A sample of 40 firms was selected from all the firms using the random sampling technique. Both qualitative and quantitative data was collected using a questionnaire that consisted of both open ended and close ended questions. Data was analyzed using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 9 publications
1
4
0
Order By: Relevance
“…Based on the coefficient value of the regression equation the SMEs characteristics become the main contributor to improved financial accessibility. The results of this study supported the results of research Nkuah, Tanyeh, & Gaeten (2013);Kira (2013);Wangmo (2015);Mulandi & Kisaka (2017) indicating that SMEs characteristics have a positive effect financial accessibility.…”
supporting
confidence: 89%
See 2 more Smart Citations
“…Based on the coefficient value of the regression equation the SMEs characteristics become the main contributor to improved financial accessibility. The results of this study supported the results of research Nkuah, Tanyeh, & Gaeten (2013);Kira (2013);Wangmo (2015);Mulandi & Kisaka (2017) indicating that SMEs characteristics have a positive effect financial accessibility.…”
supporting
confidence: 89%
“…This research will be conducted on objects of SMEs in the city of Surakarta. The study combines several previous research Wellalage, et al (2019); Mulandi and Kisaka (2017); Lusimbo and Muturi (2016) with variables that show influential tendencies . The variables consist of business characteristics, financial literacy and loan requirements for financial access to banking financial institutions.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…For the assessment of creditworthiness, several studies have shown that, even in the renewable energy sector, financial operations have the characteristics of legal isolation and isolation of financial flows [121,122]. These characteristics assimilate financing operations in renewable energy to pure project financing operations (PFOs), conducted on special purpose vehicles (SPVs).…”
Section: Methodsmentioning
confidence: 99%
“…Thus, a coefficient value of between 0.6 and 0.7 is recommended as it shows the accepted reliability. Further, Mugenda and Mugenda (2013) indicate that a 0.8 coefficient value is most recommended.…”
Section: Reliability Of the Instrumentsmentioning
confidence: 99%